Transformation of the Education System Through Cloud Computing: A Systematic Review from a Digital Economy Perspective - Yusuf , Abduel (PERFECT EDUCATION FAIRY, 2025)
Information and Communication Technology (ICT) has revolutionized various sectors, including education, facilitated by the adoption of cloud computing as an innovative solution for managing educational resources. Within the context of the digital economy, cloud computing offers cost efficiency, access flexibility, and data storage scalability, contributing to enhanced productivity within the education system. This study aims to review the literature concerning the application of cloud computing in education and its implications for the economic efficiency of education. Employing a Systematic Literature Review (SLR) methodology, this article examines 50 selected scientific publications from 2015 to 2024 relevant to this topic. The results indicate that cloud computing supports the sustainable digital transformation of education, reduces infrastructural barriers, and expands access to quality education. These findings provide a foundation for policymakers and educational practitioners in strategically adopting digital technology.